THE IMPACT OF PLAY-BASED LEARNING ON COGNITIVE DEVELOPMENT IN EARLY CHILDHOOD EDUCATION - Yuni Misrahayu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze impact of play-based learning on cognitive development in early childhood education, synthesizing findings from recent studies to provide a comprehensive understanding of how different types of play contribute to various cognitive skills in young children. This study uses a qualitative research methodology with a literature review approach to examine the impact of play-based learning on early childhood cognitive development. A literature review was selected to synthesize existing research, identify deficiencies, and provide a thorough understanding of the influence of play-based learning on children's cognitive skills. The study's findings indicate that game-based learning significantly enhances cognitive skills, including problem-solving, critical thinking, memory, and language abilities. Various types of play, such as imaginative, constructive, and interactive games, each contribute uniquely to different cognitive areas. Thus, games serve not only as entertainment but also as effective tools for promoting overall cognitive development.